Genetic insights into the crude protein and fiber content of ramie leaves - Liu, Zhiyong; Zeng, Zheng; Yang, Xiai; Zhu, Siyuan; Liu, Touming; Wang, Yanzhou (Frontiers in Plant Science, 2022)
Ramie (Boehmeria nivea L.) is a perennial plant with vigorous vegetative growth and high nutritive value that is an excellent source of green feed in China. Crude protein and fiber content are the most important traits associated with ramie forage quality; however, their genetic basis remains largely unknown. In this study, we investigated the genetic architecture of these two traits using an F2 population derived from cultivated Zhongsizhu 1 (ZSZ1) and wild Boehmeria nivea var. tenacissima (tenacissima). Linkage mapping identified eight quantitative trait loci (QTLs) in crude fiber, and one QTL in crude protein. Of these, five were further validated by association analysis. Two major QTLs for crude fiber content, CF7 and CF13, were further identified using bulked segregant analysis sequencing, and their exact physical intervals were determined via genotype analysis of F2 progenies with extremely low crude fiber content. Ten genes in the CF7 and CF13 regions showed differential expression in ZSZ1 and tenacissima leaves, including an MYB gene whole_GLEAN_10016511 from the CF13 region. Wide variation was observed in the promoter regions of whole_GLEAN_10016511, likely responsible for its downregulated expression in tenacissima. Interestingly, more fiber cells were observed in Arabidopsis with overexpression of whole_GLEAN_10016511, indicating that the downregulated expression of this gene could have an association with the relatively low fiber content in wild tenacissima. These results provided evidence that whole_GLEAN_10016511 is a logical candidate for CF13. This study provides important insights into the genetic basis underlying ramie crude protein and fiber content, and it presents genetic loci for improving the forage quality of ramie using marker-assisted selection.